2019
DOI: 10.3390/educsci9020144
|View full text |Cite
|
Sign up to set email alerts
|

Reflections of Preservice Teachers of Color: Implications for the Teacher Demographic Diversity Gap

Abstract: The reproduction of white supremacist culture in schools continues to marginalize Students of Color in a variety of implicit and explicit ways. A diverse teacher workforce not only helps to disrupt the direct effects of racism on Students of Color, but also prepares all students for successful democratic participation in a diverse global society. This article uses a portion of qualitative interview data from undergraduate Preservice Teachers of Color from a dissertation study completed within a College of Educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Novices shared how this led them to feel protective of students (Magaldi et al, 2016) and also led them to maintain “psychological distance” from White colleagues (Amos, 2020, p. 658). These responses were in tension with one another, as Olivia, a preservice teacher in Plachowski’s (2019) study, described:I didn’t feel like that was a place that I was welcome or respected or valued as an individual, let alone as somebody who identifies as a Black female and I didn’t feel like I could receive the education and experiences that I deserve as a student. .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Novices shared how this led them to feel protective of students (Magaldi et al, 2016) and also led them to maintain “psychological distance” from White colleagues (Amos, 2020, p. 658). These responses were in tension with one another, as Olivia, a preservice teacher in Plachowski’s (2019) study, described:I didn’t feel like that was a place that I was welcome or respected or valued as an individual, let alone as somebody who identifies as a Black female and I didn’t feel like I could receive the education and experiences that I deserve as a student. .…”
Section: Resultsmentioning
confidence: 94%
“…In two studies, novices shared how colleagues mistook Latino/a students’ neutral behavior for gang-related activities (Amos, 2020; Téllez, 1999). A novice in Plachowski’s (2019) study, who self-identified as a Hispanic-Latina Christian, shared how a White student in her field placement was “causing the problem and disturbing the, the Black students,” but the teacher “ignored” the White student and instead “she took away the Black students and one of the girls [who was] Latina” (p. 13). She said, “I feel like white students aren’t even punished as harshly as someone of color and who are even drawn attention or humiliated” (p. 13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…these students would get what they needed anyway" (p. 763). In several studies, teachers of color have highlighted how they experience more positive working conditions in schools serving more students who share their background, as they are more likely to be a community that affirms and values their identity (e.g., Plachowski, 2019). For example, in Haddix's (2010) study of two beginning teachers of color, a novice Black teacher said that in a predominately Black school she felt "comfort" and "like I can just be myself" (p. 112), but she said she would feel "miserable" in a predominantly White school (p. 113).…”
Section: Conceptual Framework For Sets' Working Conditionsmentioning
confidence: 99%